Advancing pedagogy of undergraduate nursing students' cultural awareness through internationalization webinars: A qualitative study. (October 2020) - Leung, Doris Y.L.; Chan, Engle Angela; Wong, Arkers K.C.; Reisenhofer, Sonia; Stenberg, Marie; Pui Sze, Chan; Lai, K.H.; Cruz, Enrique; Carlson, Elisabeth
Abstract: In today's world, nurses increasingly care for individuals from different cultures. Because culturally sensitive care can improve patient satisfaction in care, nurses need to develop cultural competence in their practice. To develop cultural competence, one option is to build cultural awareness by exposing students to nursing practices in other cultures through online internationalization-at-home activities. However, little is known about the process of cultural awareness development through internationalization activities. Therefore, this qualitative study aimed to identify the development process of cultural awareness in nursing students, who participated in a series of internationalization-at-home activities. A total of 31 nursing students from Australia, Hong Kong, and Sweden volunteered to participate in student-led learning groups. Groups consisted of two to four students from each university, who engaged in four weekly webinars and online reflections about nursing practice based on a case scenario. Data were collected from participants' ongoing reflective journal entries, and after the webinars ended, from three focus groups. A semi-structured interview guide was used to understand how the internationalization-at-home activities impacted their cultural awareness and knowledge of nursing. Data were analyzed using interpretive description. Following four levels of thematic analysis (i.e., comprehension, synthesis, theorizing, reconceptualization), we identified four themes in the development of cultural awareness: 1) nurturing reciprocity through comparisons of nursing culture; 2) discovering common ethical values of the nursing profession; 3) developing cultural awareness in nursing ideology and practice; and 4) transforming understanding of nursing in the context of their healthcare systems. By the end of the internationalization activities, students appeared to have developed relational skills to facilitate their own inner dialogue about ethical ideals of "self" and "other" in the context of being part of the global nursing community. Future research should develop and assess teaching strategies that can further facilitate the four themes in cultural awareness development.